Implementasi Internet of Things (IoT) untuk Pengawasan dan Penyiraman Otomatis pada Budidaya Cacing Tanah dengan Protokol MQTT - Jamhur Ghifari; I Gde Putu Wirarama Wedaswhara W.; Ahmad Zafrullah Mardiansyah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
The earthworm (Lumrbricus rubellus) has a special value that made it the material for cosmetics and medicine, the special value of the earth worm made it a cultivable animal. With IoT that can be implemented on every field, so was made a design of tool that will help the cultivator to keep and treat the living media of the worm. Using soil moisture sensor is the best choice because the main factor of earth worm life is the soil moisture. The ideal moisture for worm to live is 15%, with 5v submarine pump is enough to keep the soil in the best condition. Blynk application is support the development of IoT cause the apps is easy to use with lots of features and with the website that use fast and less energy MQTT protocol that suitable to developing IoT with limited resource and energy.